Perlindungan Hukum Royalti Karya Cipta Lagu Berdasarkan Peraturan Pemerintah Nomor 56 Tahun 2021 Tentang Pengelolaan Royalti Hak Cipta Lagu Dan/Atau Musik (Studi Kasus Ahmad Dhani Dan Once Mekel) - Angie Angel Lina; Fani Diyah Wulandari; Maria Theresia; Isti Qomah; Ali Ridho Saputra (Universitas Harapan Bangsa, 2023)
Song or music work is a complete copyrighted work, that song or music is a copyrighted work unit that must be protected. The case between Ahmad Dhani and Once Mekel regarding copyright began when Ahmad Dhani banned Once Mekel from performing a song created by Dewa 19. Apart from that, Ahmad Dhani demanded royalties for the song he composed, which was sung by Once Mekel. This research uses normative juridical research methods. The regulation of song copyright works according to Law Number 28 of 2014 Concerning Copyright, regulates exclusive rights including moral rights and economic rights obtained by the copyright subject. Royalties are compensation for the use of the economic rights of a creation or related product received by the creator or owner of the related rights. Government Regulation Number 56 of 2021 Concerning Song and/or Music Copyright Royalty Management, requires that everyone who makes commercial use of songs and/or music pays royalties to the creator, copyright holder, and/or owner of the related rights through institution. National Institute of Collective Management. Government Regulation Number 56 of 2021 aims to strengthen Law Number 28 of 2014 which regulates many matters relating to the principal of royalty receipts, procedures for managing royalties, distribution of royalties to responsible agencies, and royalties from users of musical works.